Puppetry and folk dramas, for non-formal education - Shah, Anupama; Joshi, Uma. (New Delhi : Sterling Publishers, 1992)
On puppetry, folk drama, street play, and role play; history and theoretical values and practical use of puppetry as an educational aid.
Includes plays in Hindi.
Includes index.
Includes bibliographical references (p. [169]-171).
Keywords: Puppet theater in education -- India; Folk drama, Indic; Puppet plays, Hindi